Fibreoptic bronchoscopy and diagnosis of pulmonary lesions in lymphoma and leukaemia. Issue 1 (January 1980) - Phillips, M J; Knight, R K; Green, M
Abstract : Fifty-six fibreoptic bronchoscopies were performed on 42 patents with Hodgkin's disease, lymphoma, or leukaemia and pulmonary complications which did not respond to conventional antibiotics. All these patients had received chemotherapy, radiotherapy, or both for the treatment of their underlying conditions. Twenty-two bronchoscopic procedures were complicated by thrombocytopenia and neutropenia, requiring platelet transfusion before bronchoscopy, and many patients were hypoxaemic. Visual examination of the tracheobronchial tree, alveolar lavage, bronchial brushing, and transbronchial biopsy were carried out as approximate. Three patients had minor pulmonary haemorrhage, and three developed a pneumothorax after transbronchial biopsy. A specific diagnosis was obtained in 14 of 18 patients (78%) with diffuse chest radiographic abnormalities, in seven of 11 patients (64%) with lobar or segmental (focal) abnormalities, in two of eight patients with small (local) lesions, and in three of five patients with hilar abnormalities. In only three patients were infections diagnosed. It is concluded that fibreoptic bronchoscopy is a useful and safe diagnostic procedure in this situation but its value depends upon the type of radiological abnormality.